1980
DOI: 10.1128/aac.18.5.709
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology, Tolerance, and Antiviral Activity of Vidarabine Monophosphate in Humans

Abstract: Vidarabine (adenine arabinoside) is a purine nucleoside useful in humans for therapy of herpes simplex virus encephalitis and herpes zoster virus infections in immunocompromised patients. However, the potential usefulness of vidaribine is limited by its poor solubility, which requires continuous infusion in relatively large volumes of intravenous fluid. Vidarabine 5'-monophosphate is highly soluble and has the advantage that it can be administered intermittently intramuscularly or intravenously. In a clinical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…Doses equal to or greater than 15 mg/kg/day can cause neurologic side effects in vivo in humans (6,10). These neurologic side effects of ara-A may be associated with high ara-H levels after ara-A infusion, particularly in patients with impaired renal function (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doses equal to or greater than 15 mg/kg/day can cause neurologic side effects in vivo in humans (6,10). These neurologic side effects of ara-A may be associated with high ara-H levels after ara-A infusion, particularly in patients with impaired renal function (30).…”
Section: Discussionmentioning
confidence: 99%
“…Since microsomal demethylating activity is highly variable, individual variations in ara-DMAP metabolism could be expected to produce variable amounts of ara-MAP, ara-A, and ara-H. Although both ara-A (IC50, 20 to 30 ,uM) and ara-H (IC50, 30 ,uM) have anti-VZV activity (14), their levels in plasma would probably be too low for these metabolites to contribute to the antiviral efficacy of ara-DMAP.…”
Section: Discussionmentioning
confidence: 99%
“…Because Ara-A has low aqueous solubility, it was given in the form of Ara-AMP in these experiments. Ara-AMP is a prodrug, which, upon dephosphorylation to Ara-A in the blood, is able to cross the cell membrane (35). As shown in Table 5, all the mice treated with either of the two drug combinations were cured.…”
mentioning
confidence: 94%
“…In neonates, however, herpesvirus encephalitis usually results from dissemination of virus acquired from maternal genital infections, and these are usually caused by HSV-2 (14). If left untreated, the mortality rate associated with this disease is approximately 70 to 80% (33,34,36,38 a 12-h period for 10 days, was found to significantly reduce the mortality due to HSV-1 encephalitis from 70 to ca. 28% among those patients (36).…”
Section: Discussionmentioning
confidence: 99%
“…The use of the more watersoluble derivative, ara-AMP, which is undergoing clinical trials for efficacy against herpesvirus infections in humans, has been suggested as a solution to this particular problem (10,37,38). Another probiem with ara-A lies in the fact that this purine.…”
Section: Discussionmentioning
confidence: 99%